Heating slagging agent for converter steelmaking under large scrap ratio and preparation method of heating slagging agent
By preparing industrial solid waste resources such as coking dust removal ash and converter dust removal ash into heating slag agents, and using the low-temperature waste heat of the converter flue gas for drying, the problem of insufficient heat and slow slag transformation in the process of lower converter steelmaking is solved, and the green smelting effect is achieved with high efficiency and low cost.
Patent Information
- Application Number
- CN202411975036.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
In the ratio of large scrap steel, there are problems such as insufficient heat, slow slag transformation, long smelting time, and reduced desulfurization and dephosphorization capacity during the steelmaking process of converter, and the existing heating agents are costly and environmentally friendly performance needs to be improved.
By preparing secondary industrial solid waste resources such as coking dust removal ash and converter dust removal ash into a heating slag agent, and using the low-temperature waste heat of the converter flue gas for drying, a heating slag agent for converter steelmaking is prepared. The heating slag agent includes 30% to 50% coking dust removal ash, 20% to 40% converter dust removal ash, 10% to 25% sintered rebate powder, and 2% to 5% composite binder, and is prepared by digestion, screening, mixing and ball forming.
It realizes the rapid increase of the converter temperature without additional metals and alloys, promotes slag recombination, increases the scrap steel ratio, reduces production costs, and has the advantages of environmental protection and resource reuse.
Smart Images

Figure CN119753271A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of converter steelmaking and metallurgical solid waste resource utilization, and in particular relates to an exothermic slag-removing agent for converter steelmaking at a large scrap steel ratio and a preparation method thereof. Background Art
[0002] The core issue of increasing the scrap steel ratio is to solve the problem of insufficient heat in the converter. At present, domestic steel production enterprises and researchers generally increase the scrap steel ratio of the converter by adjusting raw material conditions, endpoint control and smelting process. In addition, adding heating agent and preheating scrap steel are also effective ways to increase the scrap steel ratio. With the advancement of ironmaking technology and changes in metal materials for converters, the current metal raw materials for converters have the characteristics of reduced silicon content in molten iron and increased scrap steel ratio. This brings about a series of problems such as insufficient heat in the converter in the early stage of blowing, slow slagging, long smelting time, reduced desulfurization and dephosphorization capabilities, and high oxygen content in molten steel at the end. Rapidly increasing the furnace temperature in the early stage of converter blowing to promote rapid slag formation of slag-making materials for slag-gold reaction is the key to solving this series of problems.
[0003] The use of heating agents is an important auxiliary means to quickly increase the temperature of the converter molten pool. Its preparation method generally uses heating substances as the main raw materials, adds additives to adjust the composition and density, and uses a certain amount of binder to prepare and shape it for use. According to the different effective elements of the heating substances used, the heating agents for converters are generally divided into carbonaceous, silicon and aluminum heating agents. Pure carbonaceous heating agents have a light specific gravity, resulting in poor heating effect and poor slag-forming ability; silicon heating agents have a high calorific value, but are prone to increase slag volume, increase heat consumption, and are also expensive; the heating substance in aluminum heating agents is generally metal aluminum, which has the advantages of high calorific value and high efficiency of corresponding heating agents, but due to the high price of metal aluminum, the cost of steelmaking production has increased sharply, limiting its large-scale use. In addition, from the perspective of environmental protection and resource recycling, the use of recyclable materials as raw materials for heating agents has also become a trend.
[0004] Slag making is a critical link in the steelmaking process. In the converter steelmaking process, the smelting time is very short, so it is necessary to achieve rapid slag formation so that the slag has appropriate basicity, oxidizability and fluidity as soon as possible, so as to quickly eliminate impurities such as phosphorus, sulfur, silicon in the slag to below the requirements of the steel grade being made, and avoid slag overflow and splashing. The current method is to add slag-forming agents such as fluorite during smelting. The main component of fluorite is calcium fluoride. If the amount is too large, it will significantly reduce the life of the furnace lining and cause environmental fluoride pollution. At the same time, if the fluorine content in the steel slag is too much, it will also make it impossible to be used as a phosphate fertilizer, and the slag-forming effect of fluorite needs to be improved.
[0005] Coking dust ash is a kind of dust ash collected by dust collectors in the process of dry quenching cooling and coal loading. Depending on the process path, the output of coking dust ash is about 1.5% to 2.5% of the dry coke output. Coking dust ash has a high fixed carbon content, low volatile matter and sulfur content, and a good combustion rate, so it can be used in small quantities. In the converter steelmaking process, nearly 2% of various raw materials and slag-making agents are converted into converter dust ash during the smelting process. The dust ash contains a large amount of iron oxides, with a content of 50% to 65%, and the rest is other oxide impurities. Coking dust ash and converter dust ash both belong to the category of industrial solid waste (industrial solid waste). These solid wastes are generated in industrial production activities, including but not limited to dust ash generated in the coking process and dust ash generated in the steelmaking converter process. Coking dust ash and converter dust ash belong to the category of general industrial waste. If these wastes are properly handled and utilized, they can not only reduce pollution to the environment, but also achieve resource reuse and promote the development of a circular economy.
[0006] Based on the above analysis, it is necessary to design a heat-generating slag-forming agent that can not only increase the temperature of the molten pool but also accelerate the slag-forming compound function during the converter smelting process with a large scrap ratio, so as to achieve efficient, low-cost and green converter smelting with a large scrap ratio. However, there is currently no heat-generating slag-forming agent with the combined functions of efficient heat supplement and accelerated slag-forming prepared without the addition of additional metals and alloys. Summary of the invention
[0007] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide an exothermic slag-forming agent for converter steelmaking at a large scrap steel ratio and a preparation method thereof, so as to make full use of industrial solid waste resources. The prepared exothermic slag-forming agent is added to the converter to play a combined role of rapidly increasing the converter temperature and promoting slag-forming.
[0008] To achieve the above object, the present invention is implemented through the following technical solutions:
[0009] A heat-generating slag-removing agent for converter steelmaking with a large scrap ratio, comprising the following raw materials by weight percentage:
[0010] Coking dust 30%~50%; converter dust 20%~40%; sintering return ore powder 10%~25%; composite binder 2%~5%.
[0011] The fixed carbon content in the coking dust is ≥75%, the TFe content in the converter dust is ≥45%, and the TFe content in the sintering return ore powder is ≥50%.
[0012] The composite binder is a combination of at least one inorganic binder and at least one organic binder; the inorganic binder is bentonite and / or cement; and the organic binder is methyl cellulose and / or humic acid.
[0013] A method for preparing an exothermic slag-removing agent for converter steelmaking with a large scrap steel ratio comprises the following steps:
[0014] 1) Coking dust, converter dust, and sintering return ore powder weighed by weight percentage, wherein the converter dust is placed in a digestion bin for water spray digestion;
[0015] 2) Coking dust, sintering return ore powder, and converter dust after digestion are screened separately;
[0016] 3) The screened coking dust, converter dust, sintering return ore powder and composite binder are added with water and mixed and stirred to obtain a mixed raw material;
[0017] 4) Mixing the raw materials and pressing them into balls to form exothermic slag-forming agent green balls;
[0018] 5) The raw balls of the exothermic slag-forming agent are dried to obtain the finished exothermic slag-forming agent.
[0019] 5. The method for preparing a heat-generating slag-removing agent for converter steelmaking with a high scrap ratio according to claim 4, characterized in that the decomposition time of converter dust in step 1) is 10 to 12 hours.
[0020] In step 2), the percentage of the coking dust, converter dust and sintering return ore powder with a particle size of less than 200 meshes in the total weight is greater than 90%.
[0021] In step 3), the amount of water added is 2% to 5% of the total weight of the coking dust, converter dust, sintering return ore powder and composite binder.
[0022] The particle size of the exothermic slag-forming agent green balls described in step 4) is 10 to 40 mm.
[0023] The drying treatment in step 5) is a heating and dehydration treatment using the low-temperature waste heat of the converter flue gas. The drying time is 1 to 3 hours, the drying temperature is 200 to 240° C., and the moisture content of the finished exothermic slag-forming agent is <1.0%.
[0024] The finished exothermic slag-forming agent comprises the following components by mass percentage: C≥20%, TFe≥40%, the water content of the finished exothermic slag-forming agent is <1.0%, and the particle size is 10-40 mm.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1) The present invention utilizes coking dust generated in the steel production process as a heat-generating substance and converter dust ash as a slag-forming substance to prepare a heat-generating slag-forming agent without adding any additional metals and alloys. The method has a wide source of raw materials, low cost, and a simple preparation process. The prepared product has a positive effect on realizing the efficient, large-scale, and low-cost application of coking dust ash and converter dust ash secondary industrial solid waste and promoting the converter heating, slag-making, and smelting processes.
[0027] 2) In the preparation process of the present invention, the prepared exothermic slag-forming agent green balls need to be dried, and the low-temperature waste heat of converter flue gas is used for drying, which not only improves the energy utilization efficiency, but also brings significant economic and environmental benefits to steel enterprises. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The present invention is a process flow chart of a method for preparing an exothermic slag-removing agent for converter steelmaking at a large scrap steel ratio. DETAILED DESCRIPTION
[0029] The present invention is described in detail below in conjunction with the accompanying drawings, but it should be noted that the implementation of the present invention is not limited to the following embodiments.
[0030] A heat-generating slag-removing agent for converter steelmaking with a large scrap ratio, comprising the following raw materials by weight percentage:
[0031] Coking dust 30%~50%; converter dust 20%~40%; sintering return ore powder 10%~25%; composite binder 2%~5%;
[0032] The fixed carbon content in the coking dust is ≥75%, the TFe content in the converter dust is ≥45%, and the TFe content in the sintering return ore powder is ≥50%. The composite binder is a combination of at least one inorganic binder and at least one organic binder; the inorganic binder is at least one of bentonite and cement; the organic binder is at least one of methyl cellulose and humic acid.
[0033] See Figure 1 , a method for preparing a heat-generating slag-removing agent for converter steelmaking with a large scrap steel ratio, comprising the following steps:
[0034] 1) Weigh coking dust, converter dust and sintering return ore powder according to weight percentage, wherein the converter dust can be placed in a digestion bin for water spray digestion; the digestion time of the converter dust is 10 to 12 hours.
[0035] 2) Screening the coking dust, sintering return ore powder and the digested converter dust; the percentage of the coking dust, converter dust and sintering return ore powder with a particle size of less than 200 mesh after screening is greater than 90% of the total weight.
[0036] 3) Add water to the screened coking dust, converter dust, sintering return ore powder and composite binder, mix and stir evenly to form a mixed raw material; the amount of water added is 2% to 5% of the total weight of the coking dust, converter dust, sintering return ore powder and composite binder.
[0037] 4) The mixed raw materials are pressed into balls to form exothermic slag-forming agent green balls; the particle size of the exothermic slag-forming agent green balls is 10 to 40 mm.
[0038] 5) The raw balls of the exothermic slag-forming agent are dried to obtain the finished exothermic slag-forming agent.
[0039] Among them, the low-temperature waste heat of the converter flue gas is used for drying, the drying time is 1 to 3 hours, the drying temperature is 200 to 240°C, and the finished exothermic slag-forming agent contains: C ≥ 20%, TFe ≥ 40%, the water content of the finished exothermic slag-forming agent is < 1.0%, and the particle size is 10 to 40 mm.
[0040] The present invention is further explained below by way of examples.
[0041] Example 1
[0042] In this embodiment, raw materials in weight percentage are: 30% coking dust; 40% converter dust; 25% sintering return ore powder; 5% composite binder, and the raw balls are prepared by digestion → screening → adding water and mixing → pressing. The main physical and chemical indicators of the finished product of the exothermic slag-removing agent obtained after the raw balls are dried are: C ≥ 20%, TFe ≥ 50%, water content < 1.0%, and particle size 10-40mm.
[0043] Example 2
[0044] In this embodiment, the raw materials in weight percentage are: 35% coking dust ash; 35% converter dust ash; 25% sintering return ore powder; 5% composite binder, and the raw balls are obtained by digestion → screening → adding water and mixing → pressing. The main physical and chemical indicators of the finished exothermic slag-forming agent obtained after the raw balls are dried are: C ≥ 22.5%, TFe ≥ 47.5%, water content < 1.0%, and particle size 10-40mm.
[0045] Example 3
[0046] In this embodiment, the raw materials in weight percentage are: 40% coking dust ash; 30% converter dust ash; 25% sintering return ore powder; 5% composite binder, and the raw balls are obtained by digestion → screening → adding water and mixing → pressing. The main physical and chemical indicators of the finished exothermic slag-forming agent obtained after the raw balls are dried are: C ≥ 25%, TFe ≥ 45%, water content < 1.0%, and particle size 10-40mm.
[0047] Example 4
[0048] In this embodiment, the raw materials in weight percentage are: 45% coking dust ash; 25% converter dust ash; 25% sintering return ore powder; 5% composite binder, and the raw balls are obtained by digestion → screening → adding water and mixing → pressing. The main physical and chemical indicators of the finished exothermic slag-forming agent obtained after the raw balls are dried are: C ≥ 27.5%, TFe ≥ 42.5%, water content < 1.0%, and particle size 10-40mm.
[0049] Example 5
[0050] In this embodiment, the raw materials in weight percentage are: 50% coking dust ash; 20% converter dust ash; 25% sintering return ore powder; 5% composite binder, and the raw balls are obtained by digestion → screening → adding water and mixing → pressing. The main physical and chemical indicators of the finished exothermic slag-forming agent obtained after the raw balls are dried are: C ≥ 30%, TFe ≥ 40%, water content < 1.0%, and particle size 10-40mm.
[0051] According to statistics, the application effects of the exothermic slag-forming agent of the present invention under different embodiments are shown in Table 1.
[0052] Table 1
[0053]
[0054] The above data were obtained under laboratory conditions, and the steel type and molten iron conditions in all examples were consistent. In the above examples, under the converter smelting process conditions of 30% scrap steel ratio, when the converter molten pool target heating temperature was 40°C, the average heating value of the exothermic slag-forming agent was 4.55°C / t, and the average addition amount of the exothermic slag-forming agent was 8.8kg / t.
[0055] In summary, the present invention prepares the exothermic slagging agent from secondary industrial solid waste resources such as coking dust and converter dust, and uses the low-temperature waste heat of the converter flue gas to dry the exothermic slagging agent balls, thereby effectively increasing the converter melt pool temperature and promoting slagging while meeting the converter smelting requirements.
[0056] The finished exothermic slag-forming agent made by the present invention can realize the recycling and reuse of coking dust and converter dust, has a wide source of raw materials, low cost, and great economic benefits; when applied to the converter smelting process under a large scrap steel ratio, it has a good slag-forming effect while increasing the converter molten pool temperature, can effectively accelerate the converter smelting process, and further increase the scrap steel ratio.
Claims
1. A heat-generating slag-removing agent for converter steelmaking with a large scrap ratio, characterized in that: The following raw materials are included by weight percentage: Coking dust 30%~50%; converter dust 20%~40%; sintering return ore powder 10%~25%; Composite adhesive 2%~5%.
2. The exothermic slag-removing agent for converter steelmaking with a large scrap ratio according to claim 1, characterized in that: The fixed carbon content in the coking dust is ≥75%, the TFe content in the converter dust is ≥45%, and the TFe content in the sintering return ore powder is ≥50%.
3. The exothermic slag-removing agent for converter steelmaking with a large scrap ratio according to claim 1, characterized in that: The composite binder is a combination of at least one inorganic binder and at least one organic binder; the inorganic binder is bentonite and / or cement; and the organic binder is methyl cellulose and / or humic acid.
4. The method for preparing a heat-generating slag-removing agent for converter steelmaking with a large scrap ratio according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) Coking dust, converter dust, and sintering return ore powder weighed by weight percentage, wherein the converter dust is placed in a digestion bin for water spray digestion; 2) Coking dust, sintering return ore powder, and converter dust after digestion are screened separately; 3) The screened coking dust, converter dust, sintering return ore powder and composite binder are added with water and mixed and stirred to obtain a mixed raw material; 4) Mixing the raw materials and pressing them into balls to form exothermic slag-forming agent green balls; 5) The raw balls of the exothermic slag-forming agent are dried to obtain the finished exothermic slag-forming agent.
5. The method for preparing a heat-generating slag-removing agent for converter steelmaking with a large scrap ratio according to claim 4, characterized in that: Step 1) The digestion time of the converter dust removal ash is 10 to 12 hours.
6. The method for preparing a heat-generating slag-removing agent for converter steelmaking with a large scrap ratio according to claim 4, characterized in that: In step 2), the percentage of the coking dust, converter dust and sintering return ore powder with a particle size of less than 200 meshes in the total weight is greater than 90%.
7. The method for preparing a heat-generating slag-removing agent for converter steelmaking with a large scrap ratio according to claim 4, characterized in that: In step 3), the amount of water added is 2% to 5% of the total weight of the coking dust, converter dust, sintering return ore powder and composite binder.
8. The method for preparing a heat-generating slag-removing agent for converter steelmaking with a large scrap ratio according to claim 4, characterized in that: The particle size of the exothermic slag-forming agent green balls described in step 4) is 10 to 40 mm.
9. The method for preparing a heat-generating slag-removing agent for converter steelmaking with a large scrap ratio according to claim 4, characterized in that: The drying treatment in step 5) is a heating and dehydration treatment using the low-temperature waste heat of the converter flue gas. The drying time is 1 to 3 hours, the drying temperature is 200 to 240° C., and the moisture content of the finished exothermic slag-forming agent is <1.0%.
10. The method for preparing a heat-generating slag-removing agent for converter steelmaking with a large scrap ratio according to claim 4, characterized in that: The finished exothermic slag-forming agent comprises the following components by mass percentage: C≥20%, TFe≥40%, the water content of the finished exothermic slag-forming agent is <1.0%, and the particle size is 10-40 mm.